ORE MINERALIZATION, ALTERATION AND MINERALIZING HYDROTHERMAL FLUID CHARATERISTICS OF THE AWAK MAS MESOTHERMAL GOLD DEPOSIT, SOUTH SULAWESI, INDONESIA - Arifudin Idrus, Arifudin Idrus (Departmen Teknik Geologi, 2015)
Awak Mas is a mesothermal, sedimentary hosted gold deposit in Luwu, South Sulawesi, estern part of Indonesia with an approximate a measured resources of 2.13 Mio Oz. Drilling within Awak Mas including its satellite prospects, now totals 1,012 holes with an aggregate meterage of 118,081.30 meters. The Awak Mas deposit, located in the southern section of the Central Sulawesi Metamorphic Belt, is hosted within the Latimojong Formation. Predominat lithology is composed of a thick sedimentary sequence (flisch), slate, phyllites, metasandstone, metasilstone and metaclaystone, overlying basement metamorphic rock, and intruded by stocks, granite, granodiorite and diorite. Mineralization styles in Awak Mas formed in sheeted, stockwork and brecciated quartz vein, open space filling in fracture or dissaminated in host rock. Gold at Awak Mas is associated with sulphurpoor, sodic-rich fluids introduced at a relatively late stage in its tectonic history. Gold at Awak Mas, can occur as inclusion in pyrite and dissaminated as native gold in wall rock. Wall rock alteration consist of 3 type of alterations including quartz – sericite - pyrite (sericitization), albite – sericite + carbonate + clorite (albitization), and carbonate – quartz + clorite + tourmaline (carbonatization). Fluid inclusion formed in 2 phases i.e. liquid – rich, L + V where L > 30%, formed at temperature in quartz vein range of 194 o C to 320 o C, low salinity, approximately 3 to 1.2 wt.% NaCl eq. formed at depth of minimum about 390 to 1,100 m below paleowater table. CO 2 – rich inclusions are commonly taken into indiction of a non – igneous origin and typical of orogenic (mesothermal) gold deposits formed during accretionary tectonic events.